2013
DOI: 10.1007/s11596-013-1160-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-106a targets Mcl-1 to suppress cisplatin resistance of ovarian cancer A2780 cells

Abstract: Resistance to chemotherapy is a major obstacle for the effective treatment of advanced ovarian cancer. The mechanism of chemoresistance is still poorly understood. Recently, more and more evidence showed microRNAs (miRNAs) modulated many key molecules and pathways involved in chemotherapy. microRNA-106a (miR-106a) has been implicated in many cancers, but its role in ovarian cancer and drug resistance still remains unexplored. This study was to investigate whether miR-106a mediated resistance of the ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 28 publications
0
22
1
Order By: Relevance
“…In the present study, we identified the deregulation of miR-106a in ovarian cancer. miR-106a is widely expressed in diverse human tumors, including gastric, non-small cell lung, pancreatic, colorectal and ovarian cancer (6,8,9,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Previous studies showed that miR-106a acts as a tumor suppressor or an oncogene in different cancers, depending on the different cellular context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we identified the deregulation of miR-106a in ovarian cancer. miR-106a is widely expressed in diverse human tumors, including gastric, non-small cell lung, pancreatic, colorectal and ovarian cancer (6,8,9,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Previous studies showed that miR-106a acts as a tumor suppressor or an oncogene in different cancers, depending on the different cellular context.…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancers, miR-106a inhibited the growth and metastasis of NSCLC cells by decreasing phosphatase and tensin homolog (PTEN) expression (9). In ovarian cancer, upregulation of miR-106a was found to be associated with paclitaxel and cisplatin resistance (47,50).…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer (OV), miR-106a inhibited cell survival and cisplatin resistance, through downregulation of MCL1 (185); conversely expression of miR-106a was higher in cisplatin-resistant OV. miR-106a may be involved in the modulation of cisplatin-induced apoptosis by regulating PDCD4 (186).…”
Section: A Network Analysis: the Most Central Ncrnas In Chemoresistancementioning
confidence: 99%
“…In this study, miR‐193a was identified as an OVC suppressor as it was found significantly suppressed the proliferation and viability of OVC cell line A2780. Then in 2013, Rao et al found that miR‐106a inhibited OVC cell A2780's survival by suppressing MCL1 gene expression. Then there were miR‐29b, miR‐491‐5p, miR‐509‐3p,, and miR‐142‐5p that were subsequently reported to play proto‐oncogenic or anti‐oncogenic roles in OVC initiation and progression .…”
Section: Discussionmentioning
confidence: 99%